Syzygium komatiense (Myrtaceae), a new species from South Africa - Byng, James W.; Pahladsingh, Fareiza R. (Phytotaxa, 2016)
A new species of Syzygium (Myrtaceae), S. komatiense, is described from the Komatipoort area of Mpumalanga, South Africa. This species is endemic to the Komati River system on the South Africa-Mozambique border and differs from any other species in the region by its combination of terete branchlets, petiole length, often asymmetric or oblique leaf base, few-flowered inflorescence, persistent bracts and bracteoles and pseudostalk absent. Syzygium komatiense is known only from the Komati River and merits the conservation status of Critically Endangered (CR C2a(i, ii); D).